Implementation and development of the Student Assistant Program at IES San Juan Bautista (Journal of Parents and Teachers, 2018)
The Student Assistant Program constitutes an eminently educational response to prevention and intervention in cases of bullying or bullying, while generating an educational commitment in favor of the values of camaraderie, cooperation and solidarity.
Keywords: coexistence; help among equals; conflict resolution; bullying; prevention